2015
DOI: 10.1103/physrevb.91.235419
|View full text |Cite
|
Sign up to set email alerts
|

Ab initiostudy of electron-phonon interaction in phosphorene

Abstract: The monolayer of black phosphorous, or "phosphorene", has recently emerged as a new 2D semiconductor with intriguing highly anisotropic transport properties. Existing calculations of its intrinsic phonon-limited electronic transport properties so far rely on the deformation potential approximation, which is in general not directly applicable to anisotropic materials since the deformation along one specific direction can scatter electrons traveling in all directions. We perform a first-principles calculation of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
171
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(185 citation statements)
references
References 70 publications
14
171
0
Order By: Relevance
“…Our results for black-P are comparable with those previously reported by Liao et al [37]. On the other hand, quite efficient thermoelectric properties, even at moderate temperatures, are predicted for the blue-P structure, which suggest that blue-P is a strong candidate for future twodimensional thermoelectric applications.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results for black-P are comparable with those previously reported by Liao et al [37]. On the other hand, quite efficient thermoelectric properties, even at moderate temperatures, are predicted for the blue-P structure, which suggest that blue-P is a strong candidate for future twodimensional thermoelectric applications.…”
Section: Introductionsupporting
confidence: 82%
“…In addition, a remarkable increase in the Seebeck coefficient and electrical conductivity of black-P with strain induced band convergence, which leads to a maximum room temperature ZT value ∼2.1 [36] have also been reported using the same method. However, as a result of first-principles calculations, Liao et al have revealed that the maximum room temperature ZT value is only around ∼0.06 [37]. On the other hand, the relatively high performance might be expected from blue-P and therefore it is worthwhile to shed light on its thermoelectric properties, as well.…”
Section: Introductionmentioning
confidence: 99%
“…Direct calculations of the intrinsic electron-phonon scattering based on full electron and phonon dispersions have been realised only in the recent years. 79,80 The inverse relaxation time for an electron state at k being scattered by a phonon q can be written as,…”
Section: Manipulation Of Carrier Scatteringmentioning
confidence: 99%
“…16 On the theoretical side, a detailed understanding of the carrier transport dynamics is yet to be achieved with the calculated ML electron mobilities ranging widely from 170 cm 2 /Vs to over 1000 cm 2 /Vs in the literature. [17][18][19] A careful analysis, particularly on the crucial carrier-phonon interactions, is evidently called for.…”
mentioning
confidence: 99%